Practical evaluation of post-prostatectomy incontinence - Radomski, Sidney B. (Canadian Urological Association Journal, 2013)
For patients undergoing radical prostatectomy, urinary incontinence is not an uncommon postoperative complication. For some, it can resolve over time, while in others the condition persists and requires medical and/or surgical intervention. This summary provides a review of the recommended evaluations to perform in this setting.